IN VITRO PROTECTIVE EFFECT OF LEAF EXTRACT OF FICUS DELTOIDEA JACK (MORACEAE) ON BIOMARKERS OF OXIDATIVE STRESS IN THE HUMAN ERYTHROCYTES - Tkachenko, Halyna; Kurhaluk, Natalia; Buyun, Lyudmyla; Honcharenko, Vitaliy; Prokopiv, Andriy (Biota. Human. Technology, 2023)
Purpose: to investigate the antioxidant properties of the aqueous extracts derived from leaves of Ficus deltoidea using the model of human blood. For this purpose, oxidative stress biomarkers [2-thiobarbituric acid reactive substances (TBARS), content of aldehydic and ketonic derivatives of oxidatively modified proteins, total antioxidant capacity (TAC)] in the human erythrocytes after in vitro incubation with aqueous extracts derived from leaves of F. deltoidea (at a final concentration of 5 mg/mL and 0.5 mg/mL) were used. Resistance of human erythrocytes after in vitro treatment by aqueous extracts derived from leaves of F. deltoidea (at a final concentration of 5 mg/mL and 0.5 mg/mL) was evaluated by HCl-induced hemolysis using a percentage of hemolyzed erythrocytes per each 30 sec. and a total time of hemolysis. Methodology. The leaves of F. deltoidea were collected in M.M. Gryshko National Botanic Garden (Kyiv, Ukraine). Blood (10-20 mL) was obtained from normal volunteers via venipuncture (4 males and 5 females aged 28-53 years old). An erythrocyte suspension at 1% hematocrit was incubated with 4 mM phosphate buffer (pH 7.4) (control) and pre-incubated with the extract of F. deltoidea (at a final concentration of 5 mg/mL and 0.5 mg/mL, respectively) at 37 °C for 60 min. The level of lipid peroxidation was determined by quantifying the concentration of 2-thiobarbituric acid reacting substances (TBARS). The rate of protein oxidative destruction was estimated from the reaction of the resultant carbonyl derivatives of amino acid reaction with 2,4-dinitrophenylhydrazine (DNFH). The total antioxidant capacity (TAC) in the samples was estimated by measuring the TBARS level after Tween 80 oxidation. The HCl-induced resistance of erythrocytes was measured spectrophotometrically with 0.1M HCl. The significance of differences (significance level, p < 0.05) was examined using the Mann-Whitney U test. Scientific novelty. The treatment of human erythrocytes by extract derived from leaves of F. deltoidea at the final concentration of 5 mg/mL resulted in an increase of TBARS as biomarkers of lipid peroxidation and aldehydic derivatives of oxidatively modified proteins with a simultaneous decrease in the total antioxidant capacity compared to the untreated samples. On the other hand, in vitro treatment of human erythrocytes with an extract derived from leaves of F. deltoidea at the final concentration of 0.5 mg/mL resulted in the same values of TBARS level, aldehydic and ketonic derivatives of OMP, and total antioxidant capacity as the untreated samples. Extract of F. deltoidea at the final concentrations of 5 mg/mL and 0.5 mg/mL possess hemolytic properties to human erythrocyte suspension after 1-h incubation in vitro. Conclusions. The changes in the oxidative stress biomarkers using the in vitro model of human erythrocytes to evaluate the antioxidant activities of the aqueous extract derived from the leaves of F. deltoidea at the two final concentrations (5 mg/mL and 0.5 mg/mL) revealed that high concentration of extract (5 mg/mL) resulted in the increase of lipid peroxidation and protein oxidation with a simultaneous decline in the total antioxidant capacity. HCl-induced hemolysis was activated after the treatment by extract derived from the leaves of F. deltoidea at the two final concentrations. More studies are warranted in the future, to illustrate the potential and mechanisms of F. deltoidea in preventing oxidative stress using different cell models in vitro and different final concentrations of the extract. Also, further studies are warranted to identify the bioactive components that contribute to this protective effect.